OrchestraAI: A Multi-Agent Generative AI for Software Development - Holanda, João Luiz Bione da Silva; Souza, Thiago Silva de (Anais do Workshop sobre Bots na Engenharia de Software (WBOTS); 2025: Anais do II Workshop sobre Bots na Engenharia de Software, 2025)
This paper presents OrchestraAI, a multi-agent AI assistant designed to support professional software developers by combining conversational interaction with autonomous execution of development tasks, including code generation and Git version control. Unlike typical AI chatbots, OrchestraAI actively performs actions such as creating and modifying code files within a customizable local environment, preserving privacy and offering flexibility through the integration of open-source and external language models. The paper details the system’s modular architecture, which leverages LangChain and pluggable Large Language Models (LLMs), and reports qualitative results from initial evaluations. The findings indicate a strong potential for productivity improvement, along with identified limitations and proposed future improvements.